PENGARUH STRES KERJA DAN KOMITMEN ORGANSASI TERHADAP PRESTASI KERJA FASILITATOR KECAMATAN: Work stress, Organizational Commitment, Work Performance - Ena, Zet (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2020)
Job stress problems in organizations or companies become an important symptom that was observed since the onset of the emergence of demands for efficiency in work. Besides being influenced by factors originating from outside the organization, stress is also influenced by many factors. Factors originating from within the organization, therefore it is necessary to realize and understand its existence. The problem in this study is to know if there is an influence of work stress and organizational commitment and organizational commitment work performance in Kupang Regency. Data collection techniques in this study used a questionnaire. The data analysis used in this study was non parametric statistics. It illustrates that work stress is not a problem for them in improving work performance. This can be possible because they consider work stress as a form of constructive stress. The work stress experienced is a trigger for harder work. The results of this study can contribute or input for the organization concerned to learn to what extent the tendency of work stress and employee commitment in improving the work performance of their employees.